Suppression of EMI radiation noise by inductor current recoil on boost PFC. Issue 16 (10th January 2019) - Shen, Zhou; Zhao, Yang; Yan, Wei; Yu, Jin; Zhou, Mengxia; Chen, Tao; Zhu, Jiaming
Abstract : As the development of switching power and power factor correction (PFC) technology in electronic devices, there is strong transient current rate and electromagnetic interference (EMI) noise caused by switching power supply MOSFET, IGBT, and other semiconductor, which can seriously affect the normal operation of electronic devices and the electromagnetic environment. This paper established a radiation EMI model of Boost PFC circuit under critical conduction mode (CRM); extracted the high‐frequency noise current caused by Boost PFC switching device; proposed EMI radiation noise suppression technology by inductor current recoil; discussed the influence of the boost inductor and the parasitic capacitance, the transient current change rate, and the radiation EMI noise; built a Boost PFC hardware circuit; examined on EMI standardisation based on RE 101 (magnetic field radiation) and RE 102 (electric field radiation). It is proved that the boost inductor current recoil method can effectively suppress the radiation EMI noise of the Boost PFC circuit under CRM. Results show that the magnetic field radiation noise can be reduced to 2 dBpT in frequency 25 Hz–100 kHz, the radiation noise can be reduced to 20 dB V/m in frequency 100 kHz–5 MHz.